On Accident Fund – de lege lata and de lege ferenda Remarks - Jacek Wantoch-Rekowski (Prawo Budżetowe Państwa i Samorządu)
According to the forecasts, accident fund is the only fund included in the Social Insurance Fund which will have a credit balance in the coming years. This enables it to become self-sustaining – both legally and organizationally. By means of small legal changes, it is possible to normalise at least one type of insurances, without incurring any additional costs. It should be emphasized that the solution put forward by the author is not original, since the functioning of the social insurance system in the II RP was also based on legally and financially independent funds. In his study, the author points out potential directions of legal changes and justifies them.